Analisis Pengaruh Karakteristik Perusahaan Dan Penerapan Standar Akuntansi Psak No. 10 Terhadap Kualitas Laba Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Dewi Seriwati; Hendi Hendi (Global Financial Accounting Journal, 2018)
This research aims on analyzing the effects of firm characteristic and accounting standard PSAK No. 10. Firm characteristic which represent by firms size, profitability, growth, leverage, liquidity and institutional ownership towards earnings quality. The research populations were taking from the financial reports of companies listed in Indonesia Stock Exchange in the period 2010 until peroiod 2016. Using the purposive sampling method, the samples which meet the requirements for this research are 390 firms or 2.730 observations data.This research uses panel regression method to analyze the effect of independent varibles on dependent variable which measure by ratio. The observation data are thenn analyzed using eviews 7th version. The result indicates that firms size, profitability, firm growth, leverage, liquidity and PSAK No. 10 have a significant effect on earnings quality in Indonesia Stock Exchange. However, this research found that institutional ownership are insignificant to earnings quality in Indonesia Stock Exchange.